Altered activity profile of a tertiary silanol analog of multi-targeting nuclear receptor modulator T0901317. Issue 7 (1st April 2016) - Toyama, Hirozumi; Sato, Shoko; Shirakawa, Hitoshi; Komai, Michio; Hashimoto, Yuichi; Fujii, Shinya
Graphical abstract: Abstract: We report the design, synthesis, and physicochemical/biological evaluation of novel silanol derivative6 (sila-T) as a silanol analog of multi-target nuclear receptor modulator T0901317 (5 ). Compound6 showed intermediate hydrophobicity between the corresponding alcohol13 and perfluoroalcohol5 . While5 exhibited potent activities toward liver X receptor α and β, farnesoid X receptor, pregnane X receptor (PXR) and retinoic acid receptor-related orphan receptor (ROR)γ, silanol6 exhibited activity only toward PXR and RORs. Incorporation of silanol instead of perfluoroalcohol is a promising option for developing novel target-selective, biologically active compounds.